2022
DOI: 10.1177/17562848221125308
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety comparison of Helicobacter pylori eradication between vonoprazan dual therapy versus triple therapy: a systematic review and meta-analysis

Abstract: Background: As a novel drug, vonoprazan (VPZ) has been developed as a new strategy against Helicobacter pylori ( H. pylori) infections. However, whether VPZ + amoxicillin (AMO) dual therapy has a clear advantage is still unclear. Objective: To review and meta-analyze the available literature investigating the efficacy and safety of H. pylori eradication in VPZ dual therapy. Design: A systematic review and meta-analysis were conducted. Data sources and methods: We performed a systematic search in the PubMed, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The efficacy was improved (>90%) when the treatment duration was extended to 14 days. [25][26][27][28][29][30] It should be note that all the VA groups were treated with VPZ 20 mg bid and we found that high dose and low dose amoxicillin does not contribute significant difference to the cure rate. Possibly, a universally effective regimen will emerge, but it will likely require higher doses of VPZ such as 30 or 40 mg bid or tid in some regions.…”
Section: F I G U R Ementioning
confidence: 56%
See 3 more Smart Citations
“…The efficacy was improved (>90%) when the treatment duration was extended to 14 days. [25][26][27][28][29][30] It should be note that all the VA groups were treated with VPZ 20 mg bid and we found that high dose and low dose amoxicillin does not contribute significant difference to the cure rate. Possibly, a universally effective regimen will emerge, but it will likely require higher doses of VPZ such as 30 or 40 mg bid or tid in some regions.…”
Section: F I G U R Ementioning
confidence: 56%
“…Similar observations also pertain to VPZ triple therapy comparisons. As for the comparison between VA dual therapy and bismuth‐containing quadruple therapy, no significant difference was observed as well 12,25,26,28 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, before starting vonoprazan triple therapy, the local resistance rate to clarithromycin should be referenced, especially in the US, where the resistance rate exceeds 30%. Ouyang et al showed that vonoprazan dual therapy had comparable efficacy and safety profiles compared with vonoprazan triple therapy [56]. However, several journal abstracts instead of original articles were included in their meta-analysis, which could have led to potential bias.…”
Section: Discussionmentioning
confidence: 99%